Chemical Pretreatment And Thermophilic Composting Process For Rapid Biodegradation Of Rice Straw - Hosseini, Seyed Mohammad (2012)
Rice straw is one of the abundant renewable resources in the world. Until now, open field burning remains a common practice in many Asian countries for the final disposal of rice straw. The emitted pollutants from open burning of rice straw may cause adverse impact on visibility, human health, and regional air quality. Bio-transformation of rice straw to value products is an economical and environmental friendly solution for this problem. However, one of the main problems in rice straw transformation is its nonbiodegradability. The bio-oxidation rate of hydrocarbon compounds in solid state increases after such compounds transform into solution forms. Similarly, the composting of lignocellulose materials significantly enhances under thermophilic conditions. Therefore, this study focuses on time reduction of the rice straw composting process by using thermochemical pretreatment and operation under thermophilic conditions. This study investigates the operational condition of the thermochemical pretreatment process, optimize the thermochemical pretreatment, and determine the influence of thermophilic condition on the composting of pretreated rice straw. The objectives of this research are for optimization of thermochemical pretreatment process, studying the effect of pretreatment process on the stability, maturity and enhancing of rice straw composting process. The influence of mesophilic and thermophilic conditions was also investigated.